MOTIVASI KERJA GURU PROFESIONAL DALAM MELAKSANAKAN TUGAS MENGAJAR DI SEKOLAH DASAR NEGERI (SDN) KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Yuhendriyal (Universitas Negeri Padang, 2013)
The purpose of this research is to get information about work motivation of professional teacher in lesson planning, lesson implementation, evaluate the lesson result, and follow up activity at SDN District Sungai Beremas Regency Pasaman Barat. The populations of this research all the professional teacher as 39 persons (research population). The data collection is questioner by Likert scale. It has been tasted the validity and reliability of that data. The technique analysis of data used the mean formula. The result are shows that work motivation of professional teacher in their duty of teaching at SDN District Sungai Beremas Regency Pasaman Barat has high. Kata Kunci: Motivasi Kerja; Guru Profesional; Tugas Mengajar